2014
DOI: 10.3775/jie.93.1207
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production from Glucose and Cellulose Using Radio Frequency In-Liquid Plasma and Ultrasonic Irradiation

Abstract: The purpose of this study is to efficiently produce hydrogen gas from saccharide using 27.12 MHz radiofrequency (RF) in-liquid plasma with and without ultrasonic irradiation. The experiments were conducted adopting two different ultrasonic frequencies, one from a 29 kHz horn-type ultrasonic transducer and the other from a 1.6 MHz piezoelectric transducer. The glucose solution and cellulose suspension concentrations were varied from 0.5 wt% to 50 wt% and 0.5 wt% to 20 wt% respectively. Hydrogen gas was then pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…When discharge occurs in a liquid, in most cases, bubbles appear. There have been many reports which focused on bubbles in relation to the generation of plasma in a liquid by a variety of methods [32][33][34][35]. The behavior of bubbles and plasma generated by high frequency waves and microwaves is observed using a high speed camera [36][37][38][39].…”
Section: A Novel Methods For Producing Hydrogen From a Hydrocarbon Liquidmentioning
confidence: 99%
“…When discharge occurs in a liquid, in most cases, bubbles appear. There have been many reports which focused on bubbles in relation to the generation of plasma in a liquid by a variety of methods [32][33][34][35]. The behavior of bubbles and plasma generated by high frequency waves and microwaves is observed using a high speed camera [36][37][38][39].…”
Section: A Novel Methods For Producing Hydrogen From a Hydrocarbon Liquidmentioning
confidence: 99%
“…Tange et al [28] reported that high electrolyte concentration promotes plasma growth and improves the H 2 yield in the radiofrequency solution-plasma treatment of cellulose suspensions. Syahrial et al [29] found that ultrasonic irradiation improves the H 2 -production rate in the solution plasma of aqueous glucose solution. Ismail et al [30] showed that in the radiofrequency solution-plasma treatment of cellulose suspensions, gasification is enhanced when the cellulose concentration is high because cellulose enters the plasma region in granular form.…”
Section: Introductionmentioning
confidence: 99%
“…During recent years, there has been an increasing interest in plasma technology on account of the adaptability of its application in nanoparticle production [1-3], surface and coating modification [4][5][6], sterilization [7], fuel gas and hydrogen production [8][9][10][11] to name a few. A higher production rate, more straightforward reaction mechanism, and high reactivity that enhance the chemical reaction rate are some of the advantages of using plasma technology.…”
Section: Introductionmentioning
confidence: 99%